Negotiating the 'Holy Land': Cross-Cultural Encounters from Bonaparte to Blake. Issue 3 (2nd July 2020) - Otto, Peter
ABSTRACT: Napoleon's invasion of Egypt, launched in 1798, is closely linked to the birth of modern Orientalism, which Edward Said describes as the disciplines through which 'the Orient was reconstructed' in forms that brought it 'closer to Europe'. But it can also be linked to what Édouard Glissant calls 'the restlessness of the same disturbed by the other'. This perturbation is the primary object of this essay, which I explore through works by Robert Ker Porter (1777–1842), a well-known artist, traveller and diplomat; Richard Brothers (1757–1824), a popular prophet, who exerted a powerful influence on Europe's millenarian circles in the 1790s; and William Blake (1757–1827), an artist, poet, philosopher and visionary, who is now considered one of Britain's most important writers/artists. As I will argue, in the early nineteenth century, this 'restlessness' is catalyst for attempts to bring the other over to the side of the same (Porter); to bring the same over to the side of the other (Brothers); and finally to dispatch the binary oppositions that underwrite this see-saw (Blake). It is only at the end of our journey, from Napoleon to Porter, Brothers, and then Blake that a modern art and literature comes into view.